Exceptionally preserved ‘skin’ in an Early Cretaceous fish from Colombia - Alfonso-Rojas,Andrés; Cadena,Edwin-Alberto (PeerJ, 2020)
Studies of soft tissue, cells and original biomolecular constituents preserved in fossil vertebrates have increased greatly in recent years. Here we report preservation of ‘skin’ with chemical and molecular characterization from a three-dimensionally preserved caudal portion of an aspidorhynchid Cretaceous fish from the equatorial Barremian of Colombia, increasing the number of localities for which exceptional preservation is known. We applied several analytical techniques including SEM-EDS, FTIR and ToF-SIMS to characterize the micromorphology and molecular and elemental composition of this fossil. Here, we show that the fossilized ‘skin’ exhibits similarities with those from extant fish, including the wrinkles after suffering compression stress and flexibility, as well as architectural and tissue aspects of the two main layers (epidermis and dermis). This similarity extends also to the molecular level, with the demonstrated preservation of potential residues of original proteins not consistent with a bacterial source. Our results show a potential preservation mechanism where scales may have acted as an external barrier and together with an internal phosphate layer resulting from the degradation of the dermis itself creating an encapsulated environment for the integument.
Keywords: Aspidorhynchidae; Barremian; Zapatoca; South America; Soft-tissue; Molecular Paleontology